Pemberdayaan Usaha Mikro, Kecil, dan Menengah Kota Ternate (Studi Dinas Koperasi dan UKM Kota Ternate) - Adam, Syarifuddin; Rumapea, Patar; Rumawas, Wehelmina (JURNAL ILMIAH SOCIETY, 2016)
The purpose of this study was to determine how much influence the empowerment of SMEs to Community Economic Development Kota Ternate . In carrying out this study , the type of research is qualitative descriptive approach in which researchers wish to dig symptoms directly in the field with a descriptive form , this method is used due to ease writers that aims to identify and describe the corresponding problems presented previously ( Sanapiah , 2001. 52-53 ) . Based on the results of research in the field shows that MSMEs have responsibilities conceptual in nature must be expressed , one way is with the policy in the form of regulations by the government with its agencies in the field of empowerment of SMEs . Keywords: Empowerment, policy